Effectiveness of implemented global dietary interventions: a scoping review of fiscal policies - Wisdom Dogbe; Faical Akaichi; Vanessa Rungapamestry; Cesar Revoredo-Giha (BMC, 2024)
Abstract Background Although the World Health Organisation (WHO) has proposed the use of fiscal policies to mitigate consumption externalities such as overweight and obesity-related diseases, very little is known about the impacts of the different types and framing of national and/or regional fiscal policies that have been implemented over the years. There is the need to provide up-to-date evidence on the impact of fiscal policies that have been enacted and implemented across the globe. Methods We conducted a scoping review of all implemented government fiscal policies in the food and drinks sector to identify the different types of fiscal policies that exist and the scope of their impact on consumers as well as the food environment. Electronic databases such as the Web of Science and Google Scholar were used to search for appropriate literature on the topic. A total of 4,191 articles were retrieved and 127 were synthesized and charted for emerging themes. Results The results from this review were synthesized in MS Excel following Arksey & O'Malley (2005). Emerging themes were identified across different countries/settings for synthesis. The results confirms that fiscal policies improve consumers' health; increase the prices of foods that are high in fats, sugar, and salt; increase government revenue; and shift consumption and purchases towards healthier and untaxed foods. Conclusion Governments already have the optimum tool required to effect changes in consumer behaviour and the food environment.